ANALISIS KEMAMPUAN BERFIKIR KRITIS MATEMATIS DAN SELF-EFFICACY DALAM PEMBELAJARAN MATEMATIKA - Dzakiyah Kaustsari; Bambang Sri Anggoro; Novian Riskiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze students' mathematical critical thinking skills and self-efficacy in mathematics learning at MTs Negeri 2 Bandar Lampung. Critical thinking skills are essential 21st-century competencies required for students to solve problems logically and systematically, while self-efficacy reflects individuals' confidence in tackling learning challenges. This research adopts a descriptive qualitative method, collecting data through tests, questionnaires, interviews, observations, and documentation. The research subjects include grade IX students categorized into high, moderate, and low critical thinking skills, as well as mathematics teachers as supporting informants.The findings reveal that students' critical thinking skills are generally low, with only a few students meeting all critical thinking indicators. This low ability is attributed to monotonous learning processes that lack active student engagement. Furthermore, self-efficacy was found to have a positive relationship with critical thinking skills. Students with high self-efficacy demonstrated greater confidence in solving mathematical problems and exhibited more structured thinking patterns compared to those with moderate or low self-efficacy. The study recommends implementing more varied and student-centered learning models, such as problem-based learning, to enhance critical thinking skills and self-efficacy. Additionally, teachers play a crucial role in creating a supportive learning environment and providing motivation to students, which significantly contributes to improving these two aspects. Consequently, mathematics learning is expected to become more effective and contribute to the development of students' competencies in facing future educational challenges.